Precise pre-lithiation ultrathin high-capacity negative electrode with controllable lithium layer thickness and preparation method
By applying ultra-thin lithium-conducting polymer on the gloss surface of the current collector and using roll-to-roll roll pressing technology, a lithium-copper composite belt was prepared, which solved the problem of difficult control of the thickness of the lithium layer in lithium-ion batteries and improved the electrode The first week of Coulomb efficiency and energy density achieve accurate prelithization of high-capacity negative electrodes of lithium metal batteries.
Patent Information
- Application Number
- CN202411697657.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The theoretical capacity of the graphite negative electrode material of existing lithium-ion batteries is low, which is difficult to meet the demand for high-specific capacity power batteries. Moreover, the cycle performance of lithium metal batteries is degraded due to fragile SEI and irreversible lithium losses, and lacks simple and low-cost process independent preparation. Method for thin lithium metal foil.
By applying ultra-thin lithium conduction polymer on the gloss surface of the current collector, the uniform distribution of molten lithium is improved, and the lithium copper composite belt is prepared, and the negative electrode and the lithium copper composite belt are tightly combined through rolling pressure to control lithium The layer thickness achieves accurate prelithization.
It improves the uniformity of the lithium layer and the first-week Coulomb efficiency of the electrode, is suitable for large-scale preparation, has broad application prospects, and solves the challenges of energy density and mechanical brittleness of lithium metal batteries.
Smart Images

Figure CN119181773A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pre-lithiation, and in particular relates to an ultra-thin high-capacity negative electrode with a precisely pre-lithiation and controllable lithium layer thickness and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are essential for consumer electronics, electric vehicles, and stationary storage. Since their commercialization in the 1990s, they have greatly changed our lives, promoted the transition from oil- and gas-powered vehicles to pure electric vehicles, and ushered in the era of smart grids and energy intelligence. However, the large-scale popularization of pure electric vehicles still faces challenges such as "charging anxiety", "range anxiety", and cost reduction. The graphite anode material of current commercial lithium-ion batteries has a low theoretical capacity (372 mAhg -1 ), it is difficult to meet the demand for high specific capacity power batteries. Therefore, improving the rate performance and energy density of batteries while taking into account economy and safety is the key to achieving battery commercialization.
[0003] Lithium metal has 3860 mAh g -1 The theoretical specific capacity and the lowest potential platform (-3.04 V vs. Li / Li + ), and is therefore considered one of the most promising negative electrode materials. However, the continuous reaction of highly active lithium with the electrolyte will form a fragile and uneven SEI, which will continue to break and form as the volume changes during deposition / stripping, leading to problems such as particle breakage, electrical isolation and unstable growth of SEI, resulting in irreversible loss of active lithium and decreased cycle performance.
[0004] Pre-lithiation technology is an effective way to solve the irreversible lithium loss of negative electrode materials in lithium metal batteries. Practical lithium metal batteries (LMBs) require an area capacity of less than The thin lithium metal foil and the common lithium transition metal oxide cathode (area capacity of 3 to ) pairing. This requires the thickness of lithium metal to be ≤20μm. In addition, conventional lithium-ion batteries form SEI on the anode. The formation of SEI leads to the loss of active lithium and capacity in the first cycle. Due to the loss of Li, thinner Li metal foils (≤5 μm thick) are required to achieve the ideal Li compensation purpose and thus realize 100% initial Coulombic efficiency (ICE) in conventional anodes (defined as accurate pre-lithiation).
[0005] However, existing extrusion-based manufacturing techniques are capable of producing lithium metal foils with thicknesses ranging from only 20 to hundreds of microns. Extruding free-standing lithium metal foils with thicknesses less than 20 μm poses challenges to mechanical brittleness and microscale manufacturing capabilities. These thick lithium foils severely limit the energy density of lithium metal batteries. Electrochemical deposition and vacuum evaporation are the main methods for making micron-thin lithium, but these methods are costly and rely on heavier substrates, limiting their practicality. A simple and low-cost process for preparing free-standing thin lithium metal foils is a key and unsolved challenge that requires a new technology. Summary of the invention
[0006] The purpose of the present invention is to provide a high-capacity negative electrode with an ultra-thin lithium layer and a preparation method with controllable thickness, and to improve the uniform distribution of molten lithium on the current collector by coating an ultra-thin lithium-conductive polymer on the smooth surface of the current collector, and to obtain an ultra-thin lithium-copper composite tape with controllable pre-lithiation amount by regulating the preparation process. The roll-to-roll rolling realizes the close combination of the negative electrode and the lithium-copper composite tape, which can not only accurately replenish the negative electrode with lithium, but also is suitable for large-scale preparation, and has broad application prospects and advantages.
[0007] To achieve the above object, the present invention provides a method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness, comprising the following steps: S1. Disperse the lithium-conducting polymer in an organic solvent and stir evenly, then directly apply it on the smooth surface of the Cu foil, and vacuum dry it at 60-120°C for 6-12 h to obtain the polymer-modified Cu foil; S2. In an inert atmosphere, the lithium metal is heated to 200-300° C. to form a molten state, the molten lithium is transferred to two layers of opposite polymer-modified Cu foils, and the lithium metal is evenly diffused by a scraper. After completion, the excess lithium metal is removed and the two layers of ultra-thin lithium-copper composite tapes are separated to form an ultra-thin lithium-copper composite tape with an ultra-thin lithium layer on the Cu foil; S3. Roll-pressing the side of the negative electrode plate with the coating material with the ultra-thin lithium-copper composite tape. During rolling, the ultra-thin lithium layer is peeled off from the ultra-thin lithium-copper composite tape and composited with the negative electrode plate to obtain a pre-lithiated negative electrode plate.
[0008] Preferably, the lithium-conducting polymer in step S1 is any one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, ethylene-vinyl acetate copolymer, polymethyl methacrylate, polypropylene, polyethylene, n-octadecyl phosphate, polyvinylidene fluoride, and polyethylene oxide.
[0009] Preferably, the organic solvent in step S1 is any one or more of N, N-dimethylformamide, toluene, tetrahydrofuran, hexane, cyclohexane, N-methylpyrrolidone, ethyl acetate, dichloromethane, and 1,3-dioxolane.
[0010] Preferably, in step S1, 5% to 15% of the mass of the lithium-conductive polymer is added to the organic solvent, the stirring time is 5-12 h, and the coating thickness on the smooth surface of the Cu foil is 1-20 μm.
[0011] Preferably, the negative electrode sheet in step S3 is obtained by coating a coating material on a current collector and vacuum drying at 60-120° C. for 12-24 h, wherein the coating material is an electrode active material, and conductive carbon, CMC, SBR and CNT are mixed in a mass ratio of 91:2.4:1.5:5:0.1.
[0012] Preferably, the electrode active material in step S3 is any one or more of an alloy material, a silicon-carbon composite material, a silicon-oxygen compound material, a tin-based material, and a carbon-based material.
[0013] The present invention also provides a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness, which is prepared by the above-mentioned method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness.
[0014] Therefore, the present invention adopts the above-mentioned precise pre-lithiation ultra-thin high-capacity negative electrode with controllable lithium layer thickness and preparation method, and its beneficial effects are: (1) The present invention constructs an ultra-thin and uniform lithium-copper composite belt with adjustable pre-lithium amount and controllable lithium layer thickness by modifying the interface of the current collector and using an ultra-thin lithium-conductive polymer to evenly distribute molten lithium on the surface of the current collector; (2) The present invention achieves tight bonding of the negative electrode plate and the ultra-thin lithium-copper composite tape through roll-to-roll rolling, achieves accurate and uniform compensation of irreversible lithium loss of the negative electrode plate, improves the first-cycle coulombic efficiency of the electrode, is suitable for large-scale preparation, and has broad application prospects and advantages.
[0015] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a SEM image of the ultra-thin lithium-copper composite tape prepared in Example 1; Figure 2 This is a 500-fold magnified SEM cross-sectional view of the pre-lithiated alloy negative electrode after the ultra-thin lithium layer composite prepared in Example 1; Figure 3 This is an EDS image of the F element of the pre-lithiation alloy negative electrode prepared in Example 1; Figure 4 This is an EDS image of the P element of the pre-lithiation alloy negative electrode prepared in Example 1; Figure 5 The release capacity of the ultra-thin lithium-copper composite tape prepared in Example 1; Figure 6The first cycle charge and discharge curve of the button half-cell assembled for effect example 1; Figure 7 The first cycle charge and discharge curve of the button half-cell assembled in effect example 2; Figure 8 The first cycle charge and discharge curve of the button half-cell assembled in effect example 3; Fig. 9 The coulombic efficiency diagram of the two button half-cells prepared in Example 1 during 200 cycles. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0018] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0019] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.
[0020] The present invention is further described below with reference to the accompanying drawings and specific embodiments.
[0021] Embodiment 1 This embodiment discloses a method for preparing a precise pre-lithiation ultra-thin high-capacity negative electrode with controllable lithium layer thickness, comprising the following steps: S1. Disperse polyvinylidene fluoride-hexafluoropropylene in N, N-dimethylformamide, stir for 5 h, directly scrape 20 μm on the smooth surface of Cu foil, and vacuum dry at 80 °C for 12 h to obtain polyvinylidene fluoride-hexafluoropropylene modified Cu foil; S2. In an inert atmosphere, the lithium metal is heated to 200°C to form a molten state, and the molten lithium is transferred to two layers of opposite polyvinylidene fluoride-hexafluoropropylene modified Cu foils, and the lithium metal is evenly diffused using a scraper. After completion, the excess lithium metal is removed and the two layers of ultra-thin lithium-copper composite tapes are separated; S3. High entropy alloy phosphide, conductive carbon, CMC, SBR and CNT are mixed in a mass ratio of 91:2.4:1.5:5:0.1 and coated on a stainless steel sheet. The mixture is vacuum dried at 80 °C for 12 h to obtain a negative electrode sheet. The negative electrode sheet is roll-pressed with an ultra-thin lithium-copper composite tape. During the rolling process, the ultra-thin lithium layer is peeled off from the ultra-thin lithium-copper composite tape and composited with the alloy negative electrode sheet to obtain a pre-lithiated alloy electrode. Thus, a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness is obtained.
[0022] The ultra-thin lithium-copper composite strip prepared in this embodiment was observed under an electron microscope. Figure 1 As shown by Figure 1 It can be seen that the thickness of the ultra-thin lithium layer is about 5.2 μm and the thickness is uniform.
[0023] Figure 2 This is a SEM cross-sectional view of the composite of the ultra-thin lithium layer and the alloy negative electrode prepared in this embodiment. It can be seen that the thickness of the composite electrode is 19 μm, and the ultra-thin lithium layer is evenly distributed on the negative electrode sheet.
[0024] Figure 3 as well as Figure 4 These are EDS images of the fluorine element and phosphorus element distributed on the pre-lithiation alloy negative electrode prepared in this embodiment.
[0025] The separation capacity curve of the ultra-thin lithium copper composite strip prepared in this embodiment is as follows: Figure 5 As shown by Figure 5 It can be seen that the release capacity of the ultra-thin lithium-copper composite strip prepared in this embodiment is 0.78 mAh, and each component is evenly dispersed.
[0026] Embodiment 2 This embodiment discloses a method for preparing a precise pre-lithiation ultra-thin high-capacity negative electrode with controllable lithium layer thickness, comprising the following steps: Polyvinylidene fluoride was dispersed in N, N-dimethylformamide, stirred for 12 h, and then directly scraped on the smooth surface of Cu foil with a thickness of 5 μm, and vacuum dried at 80 °C for 12 h to obtain polyvinylidene fluoride modified Cu foil; S2. In an inert atmosphere, the lithium metal is heated to 250°C to form a molten state, and the molten lithium is transferred to two layers of opposite polyvinylidene fluoride modified Cu foils, and the lithium metal is evenly diffused using a scraper. After completion, the excess lithium metal is removed and the two layers of ultra-thin lithium-copper composite tapes are separated; S3. Silicon-carbon material, conductive carbon, CMC, SBR and CNT are mixed in a mass ratio of 91:2.4:1.5:5:0.1 and coated on a stainless steel sheet. The mixture is vacuum dried at 80 °C for 12 h to obtain a negative electrode sheet. The silicon-carbon negative electrode and the ultra-thin lithium-copper composite tape are roll-pressed. During the rolling process, the ultra-thin lithium layer is peeled off from the ultra-thin lithium-copper composite tape and composited with the silicon-carbon negative electrode sheet to obtain a pre-lithiated silicon-carbon electrode, thereby obtaining a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness.
[0027] Embodiment 3 This embodiment discloses a method for preparing a precise pre-lithiation ultra-thin high-capacity negative electrode with controllable lithium layer thickness, comprising the following steps: Disperse octadecyl phosphate in 1,3-dioxolane, stir for 5 h, and then directly scrape 10 μm on the smooth surface of Cu foil, and vacuum dry at 80℃ for 12 h to obtain Cu foil modified with octadecyl phosphate. S2. In an inert atmosphere, the lithium metal is heated to 200°C to form a molten state, and the molten lithium is transferred to two layers of Cu foil modified with n-octadecyl phosphate relative to each other, and the lithium metal is evenly diffused by a scraper. After completion, the excess lithium metal is removed and the two layers of ultra-thin lithium-copper composite tapes are separated; S3. Mix silicon oxide material, conductive carbon, CMC, SBR and CNT in a mass ratio of 91:2.4:1.5:5:0.1 and apply the mixture on a stainless steel sheet. Dry the mixture in vacuum at 80 °C for 12 h to obtain a negative electrode sheet. Roll-press the silicon oxide negative electrode sheet and the ultra-thin lithium copper composite tape. During the rolling process, the ultra-thin lithium layer is peeled off from the ultra-thin lithium copper composite tape and composited with the silicon oxide negative electrode to obtain a pre-lithiated silicon oxide electrode.
[0028] Effect Example 1 The button-type half-cells were assembled using the ultra-thin lithium layer composite pre-lithiated alloy negative electrode and the non-pre-lithiated alloy negative electrode prepared in Example 1, that is, the positive electrode shell, the ultra-thin lithium layer composite alloy negative electrode / non-pre-lithiated alloy negative electrode, the separator, the lithium foil, the gasket and the negative electrode shell were placed in sequence. The electrolyte was prepared by adding LITFSI and 2 wt% LiNO3 in a volume ratio of DOL:DME =1:1.
[0029] Effect Example 2 The button-type half-cells were assembled using the ultra-thin lithium layer composite pre-lithiated silicon-carbon negative electrode prepared in Example 2 and the non-pre-lithiated silicon-carbon negative electrode prepared, and the assembly method was the same as that of Example 1.
[0030] Effect Example 3 The pre-lithiated silicon oxide electrode composited with the ultra-thin lithium layer prepared in Example 3 and the non-pre-lithiated silicon oxide electrode prepared were respectively assembled into button-type half-cells, and the assembly method was the same as that of Example 1.
[0031] Experimental Testing The Xinwei test cabinet CT-4000 is used to perform testing in the voltage range of 0.01~2V or 0.01~0.8V using the constant current and constant voltage charge and discharge method.
[0032] The first cycle charge and discharge curves of button-type half-cells assembled in effect examples 1 to 3 are as follows: Figures 6 to 9 shown.
[0033] Depend on Figure 6 It can be seen that compared with the non-pre-lithiated alloy negative electrode, the first cycle efficiency of the pre-lithiated alloy negative electrode composited with the ultra-thin lithium layer in Example 1 is increased from 74.3% to 100.7%.
[0034] Depend on Figure 7 It can be seen that compared with the non-pre-lithiated silicon-carbon negative electrode, the lithium insertion capacity of the pre-lithiated silicon-carbon negative electrode composited with the ultra-thin lithium layer of Example 2 is increased from Down to , the efficiency in the first week increased from 63.2% to 89.6%.
[0035] Depend on Figure 8 It can be seen that compared with the non-pre-lithiated silicon oxide electrode, the lithium insertion capacity of the pre-lithiated silicon oxide electrode composited with the ultra-thin lithium layer in Example 3 is increased from Down to , the efficiency in the first week increased from 70.4% to 87.5%.
[0036] Effect Example 1 The coulombic efficiency of the button half-cell prepared during 200 cycles is as follows: Fig. 9 As shown in the figure, the average coulombic efficiency of the alloy negative electrode without pre-lithiation after 200 cycles is 96.7%, and the average coulombic efficiency of the pre-lithiation alloy negative electrode with ultra-thin lithium layer composite in Example 1 after 200 cycles is 98.6%. The comparison between the two shows that the pre-lithiation treatment operation is beneficial to improving the electrochemical performance of the negative electrode.
[0037] Therefore, the present invention adopts the above-mentioned precise pre-lithiation ultra-thin high-capacity negative electrode with controllable layer thickness and preparation method, constructs an ultra-thin lithium layer by modifying the surface of the current collector, and composites the ultra-thin lithium layer with the high-capacity negative electrode by simple roll-to-roll pressing to prepare a pre-lithiation electrode that can controllably and uniformly compensate for irreversible lithium loss, thereby improving the first-cycle coulombic efficiency of the electrode.
[0038] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness, characterized in that: The following steps are involved: S1. Disperse the lithium-conducting polymer in an organic solvent and stir evenly, then directly apply it on the smooth surface of the Cu foil, and vacuum dry it at 60-120°C for 6-12 h to obtain the polymer-modified Cu foil; S2. In an inert atmosphere, the lithium metal is heated to 200-300° C. to form a molten state, the molten lithium is transferred to two layers of opposite polymer-modified Cu foils, and the lithium metal is evenly diffused by a scraper. After completion, the excess lithium metal is removed and the two layers of ultra-thin lithium-copper composite tapes are separated to form an ultra-thin lithium-copper composite tape with an ultra-thin lithium layer on the Cu foil; S3. Roll-pressing the side of the negative electrode plate with the coating material with the ultra-thin lithium-copper composite tape. During rolling, the ultra-thin lithium layer is peeled off from the ultra-thin lithium-copper composite tape and composited with the negative electrode plate to obtain a pre-lithiated negative electrode plate.
2. The method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness according to claim 1, characterized in that: In step S1, the lithium-conducting polymer is any one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, ethylene-vinyl acetate copolymer, polymethyl methacrylate, polypropylene, polyethylene, octadecyl phosphate, polyvinylidene fluoride, and polyethylene oxide.
3. The method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness according to claim 1, characterized in that: In step S1, the organic solvent is any one or more of N, N-dimethylformamide, toluene, tetrahydrofuran, hexane, cyclohexane, N-methylpyrrolidone, ethyl acetate, dichloromethane, and 1,3-dioxolane.
4. The method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness according to claim 1, characterized in that: In step S1, 5% to 15% of the mass of the lithium-conductive polymer of the organic solvent is added, the stirring time is 5-12 h, and the coating thickness on the smooth surface of the Cu foil is 1-20 μm.
5. The method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness according to claim 4, characterized in that: The negative electrode sheet in step S3 is obtained by coating a coating material on a current collector and vacuum drying it at 60-120° C. for 12-24 hours. The coating material is an electrode active material, and conductive carbon, CMC, SBR and CNT are mixed in a mass ratio of 91:2.4:1.5:5:0.
1.
6. The method for preparing a precisely pre-lithiated ultra-thin high-capacity negative electrode with controllable lithium layer thickness according to claim 5, characterized in that: In step S3, the electrode active material is any one or more of an alloy material, a silicon-carbon composite material, a silicon-oxygen compound material, a tin-based material, and a carbon-based material.
7. Precise pre-lithiation ultra-thin high-capacity negative electrode with controllable lithium layer thickness, characterized in that: The method for preparing an ultra-thin high-capacity negative electrode with a precisely pre-lithiated structure and controllable lithium layer thickness is adopted according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of metallic lithium strip and metallic lithium strip prepared by the same
CN104993094A
Metal lithium composite cathode as well as preparation method and application thereof
CN109411694A
Ultra-thin metal lithium complex, preparation method and application thereof
CN109873122A
Method for preparing lithium-supplementing negative electrode and lithium-supplementing negative electrode
CN114361398A
Ultrathin metal lithium composite material and preparation and application thereof
CN116435496A
